Hydrodeoxygenation of bio-derived anisole to cyclohexane over bi-functional IM-5 zeolite supported Ni catalysts. Issue 12 (9th October 2019) - Tu, Chunyan; Chen, Junwen; Li, Wenlin; Wang, Hongyan; Deng, Kaixi; Vinokurov, Vladimir A.; Huang, Wei
Abstract : IM-5 zeolite supported Ni nanoparticles were demonstrated to be an efficient bi-functional catalyst for the hydrodeoxygenation of anisole to cyclohexane. Abstract : The catalytic properties of three IM-5 supported nickel catalysts prepared by incipient wetness impregnation, melt infiltration and hydrothermal synthesis, respectively, were evaluated by hydrodeoxygenation (HDO) of bio-derived anisole to cyclohexane and compared with those of γ-Al2 O3 and ZSM-5 supported nickel catalysts. The IM-5 zeolite was found to be the best support for the reaction in terms of anisole hydroconversion. The three IM-5 supported nickel catalysts achieved 83.1–100% anisole conversion at a reaction temperature of 200 °C while the conversion of anisole only reached 0.5% for Ni/γ-Al2 O3 and 34.2% for Ni/ZSM-5-m. The nickel species were better dispersed on the IM-5 supported catalysts with higher mesoporosity and moderate acidity when compared to ZSM-5 supported samples. Moreover, the fabricated Ni/IM-5-h catalyst by hydrothermal synthesis could display excellent hydrodeoxygenation performance with anisole conversion of 98.7% and nearly 100% cyclohexane selectivity at 200 °C. The highly dispersed Ni species demonstrated by TEM and CO-IR spectra may be responsible for the high activity and selectivity in anisole hydrodeoxygenation. Besides, the state of metal sites is crucial for the selectivity to hydrocarbons as demonstrated by catalyst reduction at different temperatures. In addition, different reaction parameters such as reaction time, reaction temperature and hydrogen pressure were studied in detail to reveal the reaction pathway of anisole hydrodeoxygenation.